2013
DOI: 10.1007/s40136-013-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology and Clinical Implications of the Laryngeal Adductor Reflex

Abstract: The laryngeal adductor reflex (LAR) is an involuntary protective response to stimuli in the larynx. The superior laryngeal nerve (SLN) acts as the afferent limb and the recurrent laryngeal nerve (RLN) as the efferent limb of this reflex, which is modulated by the central nervous system. Perhaps the most clinically significant application of the LAR is its use in laryngopharyngeal (LP) sensory discrimination testing. Importantly, aberrations in the LAR may predict dysphagia or portend clinical phenotypes of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Here, an air pulse is applied to the anterior pharyngeal wall through an additional channel of the endoscope. The pressure of the air pulse can be varied and thus, a threshold value is determined at which the laryngeal adductor reflex is triggered . The clinical relevance of the air pulse method has been discussed controversially, and conflicting results have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, an air pulse is applied to the anterior pharyngeal wall through an additional channel of the endoscope. The pressure of the air pulse can be varied and thus, a threshold value is determined at which the laryngeal adductor reflex is triggered . The clinical relevance of the air pulse method has been discussed controversially, and conflicting results have been published.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure of the air pulse can be varied and thus, a threshold value is determined at which the laryngeal adductor reflex is triggered. [36][37][38] The clinical relevance of the air pulse method has been discussed controversially, and conflicting results have been published. In one study, the absence of the laryngeal adductor reflex was associated with aspiration and penetration in a mixed collective of dysphagic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the regions to touch for testing sensation: a patient's aryepiglottic folds (Langmore et al, 1988;Leow, Beckert, Anderson, & Huckabee, 2012;Onofri et al, 2014), arytenoids (Langmore et al, 1988;Onofri et al, 2014) or epiglottis (Langmore et al, 1988). Studies have reported five acceptable positive responses to the touch of an endoscope: patient report when they feel the touch (Kaneoka, Krisciunas, Walsh, Raade, & Langmore, 2015;Leow et al, 2012;Sato et al, 2002), an LAR (Domer, Kuhn, & Belafsky, 2013;Onofri et al, 2014), a cough, a gag, or a swallow (Langmore et al, 1988;Leow et al, 2012). However, several issues remain unclear regarding the touch method.…”
mentioning
confidence: 99%
“…The laryngeal adductor refl ex (LAR) [ 4 ], also called the glottic closure refl ex, is a brainstem-mediated, involuntary refl ex arc, which prevents substances from inappropriately entering the airway. The LAR is a bilateral thyroarytenoid (TA) muscle response to mechanical or chemical irritation of the laryngeal mucosa.…”
Section: Laryngeal Adductor Reflexmentioning
confidence: 99%
“…The LAR is a bilateral thyroarytenoid (TA) muscle response to mechanical or chemical irritation of the laryngeal mucosa. The afferent limb of this refl ex arc is formed by the superior laryngeal nerve, while the recurrent laryngeal nerve acts as the efferent limb [ 4 ].…”
Section: Laryngeal Adductor Reflexmentioning
confidence: 99%